2019
DOI: 10.3390/molecules24091738
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from Cell Suspension Cultures of Strawberry (Fragaria x ananassa Duch): Cytotoxic Effects on Human Cancer Cells

Abstract: Natural compounds are emerging as agents for the treatment of malignant diseases. We previously showed that extracts from in vitro cell suspension cultures of strawberry reduced murine melanoma cell proliferation, as shown for fruit extracts. In this work, chromatographic, mass spectrometric, and spectrophotometric analyses were carried out to identify the bioactive compound exerting the detected cytotoxic activity. Moreover, aiming to confirm the anti-proliferative activity of the extracts against both paedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In vitro techniques may represent a tool for improving flavonoid biosynthesis and availability throughout the year to overcome these problems. Different plant in vitro cultures (i.e., callus, cell suspension cultures, organ, and hairy root cultures) and transformation techniques have been utilized to investigate and to improve the synthesis of these important molecules [31][32][33][34][35]. Several approaches have been taken into account, such as selecting high-yielding lines, precursor feeding, and the use of elicitors [36].…”
Section: Flavonoids and Biotechnologymentioning
confidence: 99%
“…In vitro techniques may represent a tool for improving flavonoid biosynthesis and availability throughout the year to overcome these problems. Different plant in vitro cultures (i.e., callus, cell suspension cultures, organ, and hairy root cultures) and transformation techniques have been utilized to investigate and to improve the synthesis of these important molecules [31][32][33][34][35]. Several approaches have been taken into account, such as selecting high-yielding lines, precursor feeding, and the use of elicitors [36].…”
Section: Flavonoids and Biotechnologymentioning
confidence: 99%
“…Many studies have reported the higher intake of fruits and vegetables can reduce the risk of developing chronic disease [ 3 , 4 ]. Berries contain many bioactive compounds and are reported to have high antioxidant [ 5 ], antitumor [ 6 , 7 ] and anti-inflammatory activities [ 8 ]. Among the various berries such as blueberries, strawberries, blackberries, and cranberries are consumed not only in raw form but also in the form of beverages, yoghurt, jelly, and jam as processed foods.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various berries such as blueberries, strawberries, blackberries, and cranberries are consumed not only in raw form but also in the form of beverages, yoghurt, jelly, and jam as processed foods. In many in vitro and in vivo experiments, berries are known to reduce the risk of cancer because they contain abundant amounts of phenolic acid, flavonoids, tannins, stilbenes, vitamin C, and vitamin E [ 6 , 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ellagitannin-enriched fraction also induced necrosis and apoptosis in the threated cells, decreased chymotrypsin-like activity of the 26S proteasome, impaired autophagic flux, promoted the accumulation of ubiquitinated proteins, and decreased the expression of several proteasome subunits. Lucioli et al [91] evaluated the influence of hydroalcoholic extracts (methanol, ethanol, isopropanol) from in vitro cell suspension on the proliferation of several cancer cells (neuroblastoma, colon, and cervix carcinoma cell lines). The extracts induced a statistically significant reduction of cell growth but did not affect the human fibroblasts from healthy donors.…”
Section: Other Potential Applicationsmentioning
confidence: 99%